Wavelet analysis of the ionospheric response at mid-latitudes during the april 2000 storm using magnetograms and vTEC from GPS - Fernández, Laura Isabel (2012)
In this work we pursue the idea of computing a parameter that allows us to estimate the local ionospheric response to a geospheric event that triggers an ionospheric storm. For that, wavelet technique has been chosen because of its ability to analyze non-stationary signals. The advantage of the time-frequency analysis method called Wavelet Transform resides in providing information not only about the frequencies of the event but also about its location in the time series. Specifically, we compute the Scale Average Wavelet Power (SAWP) of two parameters that describe the local geomagnetic field variation at the Earth surface caused by a geospheric storm and ionospheric response to the storm event. In particular, we propose the time delay between the maximum values of SAWP applied to the vTEC (vertical Total Electron Content) and the horizontal component of the geomagnetic field (H) variations as parameters to characterize the local behavior of the ionospheric storm. We applied the parameter to the geomagnetic and ionospheric disturbances caused by a coronal mass ejection (CME) that took place on April 4, 2000. We used vTEC values computed from GPS observations and H at the surface of the Earth, measured in stations near to each GPS station chosen. The vTEC values used came from the GPS permanent stations belonging to the global IGS (International GNSS Service) network. We chose stations located at magnetic mid-latitudes. Moreover, three-longitude bands representing the ionospheric behavior at different local times (LT) were studied. Because the April 2000 storm has been extensively studied for many authors, the results are compared with those in the literature and we found a very good agreement as expected.